Sejarah Perkembangan Hadits Dari Zaman Rasulullah Hingga Saat Ini - Saleh, Musyirah; Ilyas, Abustani; Hafid, Erwin (CV. SINAR HOWUHOWU, 2026)
Hadith constitutes the second primary source of Islamic teachings after the Qur’an and plays a fundamental role in the formation of Islamic law, theology, and religious practice. The historical development of Hadith unfolded through several distinct periods, each characterized by specific historical and scholarly objectives. This study aims to analyze the correlation between the objectives of each period in the development of Hadith from the era of the Prophet Muhammad (peace be upon him) to the contemporary period and the forms of transmission, codification, and methodological consolidation of Hadith scholarship that emerged therein. This research employs a library research method with a historical-descriptive approach, drawing upon classical and contemporary sources in Hadith studies. The findings indicate that each phase of Hadith development pursued specific and interconnected objectives, collectively forming a solid foundation for the discipline of Hadith studies up to the present day. This study is expected to contribute to the academic discourse by offering a comprehensive understanding of the historical dynamics and underlying purposes of Hadith periodization.